A 2-year calorie restriction intervention may reduce glycomic biological age biomarkers – a pilot study - Pribić, Tea; Das, Jayanta K.; Đerek, Lovorka; Belsky, Daniel W.; Orenduff, Melissa; Huffman, Kim M.; Kraus, William E.; Deriš, Helena; Šimunović, Jelena; Štambuk, Tamara; Frkatović-Hodžić, Azra; Kraus, Virginia B.; et al. (npj aging, 2025)
In this pilot study, a subset of CALERIE Phase 2 (No. NCT00427193, registered 25th Jan 2007) participants ( n = 26) were evaluated for the effects of 2 years of 25% calorie restriction (CR) on N-glycosylation of IgG, plasma, and complement C3, as well as IgG-based biological age (GlycAge). Plasma samples were collected at baseline (BL), 12 (12mo), and 24 months (24mo). IgG galactosylation was higher at 24mo compared to BL ( p = 0.051) and increased from 12mo to 24mo ( p = 0.016); GlycAge decreased over the same period ( p = 0.027). GlycAge was positively associated with TNF-α ( p = 0.030) and ICAM-1 ( p = 0.017). Between BL and 24mo, plasma high-branched glycans declined ( p = 0.013), bisecting GlcNAcs increased in both plasma ( p < 0.001) and IgG ( p = 0.01), complement C3 protein ( p < 0.001), C3-Man9 ( p < 0.001), and C3-Man9Glc1C3 ( p = 0.046) were reduced. The absence of a control group warrants cautious interpretation.